QUALITY OF WATER SERVICE AT PEPITO RESTAURANT COMFORTA HOTEL DUMAI - Hartika, Reni; Sidiq, Rd. Siti Sofro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This study assesses the service quality at Comforta Hotel's Pepito restaurant in Dumai. Using qualitative descriptive methods and data from 100 respondents through observation, interviews, and questionnaires, the research found that the service quality of waitstaff needs improvement due to significant complaints, highlighting the importance of enhancing service quality in the hotel industry. Keywords: service, quality